2017
DOI: 10.1542/peds.2016-3459
|View full text |Cite
|
Sign up to set email alerts
|

Eggs in Early Complementary Feeding and Child Growth: A Randomized Controlled Trial

Abstract: The findings supported our hypothesis that early introduction of eggs significantly improved growth in young children. Generally accessible to vulnerable groups, eggs have the potential to contribute to global targets to reduce stunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
252
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(288 citation statements)
references
References 24 publications
12
252
5
3
Order By: Relevance
“…In addition, due to missing information in vitamin A‐rich vegetables in 2007 and other vegetables in 2007 and 2014, fruit and vegetable consumption could have been underestimated in the corresponding years; (c) other fruits and vegetables, which also declined from ~50% in 2007 to ~22% in 2014 that may not entirely be explained by seasonality (Figure S5); and (d) eggs, which were fed to less than a third of children and even fewer among children aged 6–11 months. Recent evidence from Latin America shows the potential of introducing eggs early in children's diets both in increasing the intake of protein and improving linear growth in young children (Iannotti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to missing information in vitamin A‐rich vegetables in 2007 and other vegetables in 2007 and 2014, fruit and vegetable consumption could have been underestimated in the corresponding years; (c) other fruits and vegetables, which also declined from ~50% in 2007 to ~22% in 2014 that may not entirely be explained by seasonality (Figure S5); and (d) eggs, which were fed to less than a third of children and even fewer among children aged 6–11 months. Recent evidence from Latin America shows the potential of introducing eggs early in children's diets both in increasing the intake of protein and improving linear growth in young children (Iannotti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Eggs are an inexpensive and more accessible high protein source for the low-income population than fortified foods. This study showed that the ingestion of one egg per day can reduce the prevalence of stunting by 47% and underweight by 74% compared with the control group that did not receive eggs (Iannotti, et al, 2017). This device will be able to reduce the gap between the access to protein and children of low-income; trying to lessen the social problem of malnutrition.…”
Section: Social Solutionmentioning
confidence: 86%
“…In the United Kingdom, the Food Foundation, a non-profit organization working to improve nutrition, collaborated with the creative agency ifour in late 2017 to create messages and images that tap into children's interest in superheroes to encourage them to eat vegetables. The impact of this has not yet been rigorously evaluated, but a related initiative targeting households in a province of Ecuador in 2015 increased egg consumption to one a day in 6-to 9-month-olds, and improved growth 15 . Providing such incentives will boost consumer demand and thus encourage companies to meet it.…”
Section: Millionmentioning
confidence: 99%